Prinsip Publisitas dalam Pendafataran Jaminan Fidusia Secara Online - Dwi Fefri Kurniasari; Dian Alfridha Rosyad; Tenny Pantow Tambariki; Irwansyah Giovani ibrahim; Charisma Adilaga Sugiyanto (JURNAL RECHTENS, 2026)
Along with the development of information technology, the Fiduciary Guarantee registration mechanism has shifted to an integrated online electronic system. This study aims to analyze whether online fiduciary guarantee registration meets the principles of publicity and is binding on third parties. This study uses a normative legal research method with a statutory approach and a conceptual approach. The conclusion obtained is the principle of publicity which is one of the fundamental principles in online fiduciary guarantee registration. Online fiduciary registration still provides equal legal protection for creditors and remains binding on third parties, as long as the registration process is carried out in accordance with applicable provisions. Legally, online fiduciary registration still fulfills the elements required to bind third parties, namely: registration in the official state register, the existence of a fiduciary guarantee certificate, certainty of the registration date, and legal recognition of electronic documents. With the fulfillment of these elements, there is no fundamental difference between manual registration and online registration in terms of binding on third parties